Socioeconomic and gender group differences in early literacy skills: a multiple-group confirmatory factor analysis approach - Julia Ai Cheng, Lee; Al Otaiba, Stephanie (Routledge, 2015)
Socioeconomic status and gender are important demographic variables that strongly relate to academic achievement. This study examined the early literacy skills differences between 4 sociodemographic groups, namely, boys ineligible for free or reduced-price lunch (FRL), girls ineligible for FRL, boys eligible for FRL, and girls eligible for FRL. Data on kindergarteners (N = 462) were analysed using multiplegroup confirmatory factory analysis. Early literacy skill differences between boys and girls are more nuanced than previously reported; subsidy status and gender interact. Both boys and girls from high-poverty households performed significantly lower than the girls from low-poverty households in alphabet knowledge, phonological awareness, and spelling. There were gender gaps, with a female advantage, among children from high-poverty households in alphabet knowledge and spelling and among children from low-poverty households in alphabet knowledge. These results highlight the importance of employing methodologically sound techniques to ascertain group differences in componential early literacy skills.